Contenidos virtuales deportivos y su incidencia en el desarrollo cultural en jóvenes y adultos del sector La Ercilia, cantón El Empalme, año 2022 - Cano Mora, Verónica Liliana (2022)
At present there is no doubt about the importance of sports disciplines and how they influence society, both in its show facet and in its practice dimension. The daily media such as television, radio dedicate hours of live transmission, while in the newspapers their main covers are dedicated to the sports disciplines that have stood out the most, without leaving behind the social networks and all the platforms that They have also created virtual content that informs about all the events that involve the practice of some sport of interest that is at the forefront. Journalism as a social phenomenon has the mission of arduously guiding and educating society by responsibly informing what is presented whatever the means of communication used, thus avoiding falling into misrepresentation of information or alteration to capture a greater public, that the only thing that affects is losing credibility and being described as a show content that does not contribute to the cultural development of society.